Implementasi Metode Flat Pada Sistem Informasi Akuntansi Pinjaman Sebagai Perhitungan Angsuran Berbasis Web - Ahmad Ashifuddin Aqham (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2024)
The need for technology is greatly needed by various groups, both in the world of education, in companies and government agencies as a solution to these problems. One of them is implementing an accounting information system for inputting, processing or reporting accounting in the company. This application can produce data processing quickly and accurately. This certainly saves a lot of time and also reduces errors that occur when work is done manually. Likewise with cooperatives, cooperatives also need to use an accounting information system to make their work faster and more accurate. The activities carried out at Primkopti "Harum" Kendal Regency are in the field of savings and loans. The process of recording loans at Primkopti "Harum" becomes ineffective and there is a risk of errors in information that is not accurate and fast, because the recording process is repetitive. For reporting, we still use Ms. Excel, which still requires data processing first from the books, both loans and installments, so there are often delays in submitting reports to management. Therefore, with a computerized system that can process customer data, collateral data, journals, loan and installment transactions, and also reports that will be made by Primkopti "Harum" will be valid, especially in calculating installment interest costs, using Macromedia Dreamweaver software 8, PHP programming language, and MySQL database. The results of the programming created help reduce errors in data entered, errors in interest calculations, financial reports are produced more quickly and effectiveness and efficiency can be achieved.